Radiographic features of congenital thumb duplication type C2 of Wu et al. classification: new subtypes and surgical strategies - Wu, JianPing; Shi, WeiZhe; Zhao, Hai; Li, JingChun; Li, YiQiang; Hong, Kai; Yuan, Zhe; Zhu, MingWei; Liu, YuanZhong; Canavese, Federico; Xu, HongWen (Frontiers in Pediatrics, 2024)
This study aimed (i) to evaluate the radiographic characteristics of patients with CTD type C2 according to the classification of Wu et al., (ii) to describe the various subtypes of type C2 CTD and (iii) to propose a classification system that allows the identification of different surgical strategies based on the radiographic anatomy of this specific subtype of duplication.We retrospectively reviewed 92 patients ( 92thumbs) with type C2 CTD according to Wu et al. Classification in our institution between August 2015 and April 2021. All CTDs were classified according to the interphalangeal (IP) joint alignment of the main thumb at the posteroanterior (PA) radiograph of the thumb before operation: type I (no deviation), type II (ulnar deviation), and type III (radial deviation).All CTDs (n=92) could be classified according to the proposed classification system: 76 (82.6%) were type I, 10 (10.9%) were type II and 6 cases were type III (6.5%).According to the Kim subtypes system there were 55 (59.8%) type 1, 24 (26.1%) type 2, and 13 (14.1%) type 3.The suggested classification completes the Wu et al. system and has potential to guide surgical treatment in children with type C2 CTD.